HUBUNGAN PERUBAHAN FISIK DENGAN KEJADIAN DEPRESI PADA LANSIA - Prihananto, Dhian Ika; Mudzakkir, Muhammad (Universitas Pesantren Tinggi Darul Ulum, 2024)
The physical changes experienced by the elderly influence the psychological problems of the elderly. Depression is a psychological disorder that often attacks the elderly. If this problem is not addressed, it can cause physical and mental disorders and hinder social functioning. Not only that, depression can also make other chronic health problems more difficult to treat. The aim of this study was to determine the relationship between physical changes and the incidence of depression in the elderly. This research is quantitative research with a case-control approach. The sampling technique was consecutive sampling of 52 respondents. The research instruments were a depression measurement scale in the elderly (beck) and an interview questionnaire. Analysis with chi-square test. The results of the research were that there were 8 respondents who could not accept physical changes in the case group and 3 respondents in the control group. The results of the chi-square test obtained a value of p=0.174 OR=3.407 95%CI=0.789 – 14.720. The conclusion is that there is no relationship between physical changes and the incidence of depression in the elderly. Keywords: Physical changes, depression in the elderly.